Spiritual but not religious (SBNRS): A critical analysis of Sam Harris’s waking up - Sadia Yousaf Zia; Dr. Humaira Ahmad (jihat-ul-islam, 2025)
Religion and spirit always go side by side. In this era spirit and religion are studied separately with the thought of an anti-religious phenomenon is there with its vast impacts. Non-religious minds and religious ones have a lot of things that differ, they have spiritual struggles. The theme arises in the name of non-religious spirituality (NRS). The thought prevailed in the west and now in the east in reverse of the religious institutional thought and spirituality. Religious disputes created an image to the world that is nontolerant and companionate, rising a question of God existence and self-existence. Thus, giving rise in Atheism, nihilism, free thinking. The thinking of spirituality also has gone in another side with superstitions and spiritual meditation. The religious narrative is there but denied. Practices amalgamated with spirituality. The study introduces the phenomenon and the theorizer of SBNR who initiated it with potential. This article will critically analyze the theory presented in waking up with its impact in a broader sense.